A systematic review of post-pancreatectomy haemorrhage management stratified according to ISGPS grading. Issue 7 (July 2022) - Maccabe, Thomas A.; Robertson, Harry F.; Skipworth, James; Rees, Jonathan; Roberts, Keith; Pathak, Samir
Abstract: Background: Morbidity and mortality from post-pancreatectomy haemorrhage (PPH) remains high. The International Study Group of Pancreatic Surgery (ISGPS) published guidelines to standardise definitions of PPH severity, management and reporting. This study aimed to i) identify the number of studies reporting PPH using ISGPS guidelines (Grade A, B or C) and ii) describe treatment modality success by grade. Methods: A systematic literature review was performed, identifying studies reporting PPH by ISGPS Grade and their subsequent management. Results: Of 62 studies reporting on PPH management, 17 (27.4%) stratified by ISGPS guidelines and included 608 incidences of PPH: 48 Grade A, 274 Grade B (62 early, 166 late, 46 unspecified) and 286 Grade C. 96% of Grade A PPH were treated conservatively. Of 62 early Grade B, 54.8% were managed conservatively and 37.1% surgically. Late Grade B were managed non-operatively in 25.3% (42/166), with successful endoscopy in 90.9% (10/11) and angiography in 90.3% (28/31). In Grade C, endoscopic treatment was successful in 64.4% (29/45) and angiography in 90.8% (108/119). Surgical intervention was required in 43.5% early Grade B, 7.8% late Grade B and 33.2% Grade C. Conclusion: PPH grading is underreported and despite guidelines, inconsistencies remain when using definitions and reporting of outcomes.